Communication Strategies in Preventing Student Rule Violations - Tri Hardiansyah; Wawan Hernawan; Budhi Waskito (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
Juvenile delinquency remains one of the major social problems continuously affecting Indonesia. Assuming that students spend approximately 8 to 9 hours at school, they interact more within the school environment than at home. Teachers and peers thus play a significant role in shaping students’ character. The purpose of this study is to synthesize school strategies in communicating with students to prevent violations at SMA Negeri 10 Bandar Lampung. This research employed a descriptive method with a qualitative approach. Data were collected through documentation, observation, and interviews, and analyzed using the Miles & Huberman model. The findings indicate that communication strategies are oriented toward maturity and empathy, conducted in a two-way manner, providing space for dialogue, gradual, non-intimidating, utilizing soundproof safe spaces, and based on student data. This approach is consistent with the principles of Social Penetration Theory, which emphasizes the depth and breadth of self-disclosure. The outcomes of this implementation include increased student openness, the establishment of trust, and more cooperative follow-up planning.